Tear down this wall : on the persistence of borders in trade - Volker Nitsch; Nikolaus Wolf (Center for Economic Studies and ifo Institute (CESifo), 2009)
Why do borders still matter for economic activity? The reunification of Germany in 1990 provides a unique natural experiment for examining the effect of political borders on trade both in the cross-section and over time. With the fall of the Berlin Wall and the rapid formation of a political and economic union, strong and strictly enforced administrative barriers to trade between East Germany and West Germany were eliminated completely within a very short period of time. The evolution of intra-German trade flows after reunification then provides new insights for both the globalization and border effects literatures. Our estimation results show a remarkable persistence in intra-German trade patterns along the former East-West border; political integration is not rapidly followed by economic integration. Instead, we estimate that it takes at least one generation (between 33 and 40 years or more) to remove the impact of political borders on trade. This finding strongly suggests that border effects are neither statistical artefacts nor mainly driven by administrative or red tape barriers to trade, but arise from economic fundamentals.
Keywords: F14; F15; 330; integration; home bias; globalization; Interregionaler Handel; Grenze; Wirtschaftsintegration; Globalisierung; Alte Bundesländer; Neue Bundesländer; Nationale Einheit; Deutschland